Pluralisme Hukum Dalam Tradisi Perkawinan Sasuku Pada Masyarakat Minang - Irzak Yuliardy Nugroho; Mufidah CH; Suwandi (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2022)
This study discusses the tradition of banning sasuku marriages in the Minang community. These rules resulted in many legal rules that run on the Minang community, customary law, Islamic law, and state law. The number of legal rules makes the marriage law of the Minang community seem gray, on the one hand, they must comply with Islamic law and state law which does not regulate the prohibition of ethnic marriage. Meanwhile, on the other hand, there are customs that make rules regarding the prohibition of sasuku marriages. This research uses a qualitative paradigm, with the type of research being a conceptual approach. The data used are secondary data from several journals, which are then combined with the legal facts of the Minang community regarding the prohibition of ethnic marriage. This conclusion shows that the occurrence of legal pluralism in Minang society is a social necessity. The prohibition of tribal marriages in addition to having an impact on the social order also threatens the existence of Islamic law in the aspect of marriage in terms of determining a mate, including abolishing Indonesian marriage law regarding marriages carried out on voluntary terms from both parties.